2015
DOI: 10.1016/j.jpsychores.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and behavioral problems in late-identified Indonesian patients with disorders of sex development

Abstract: Indonesian patients with DSD who were untreated for most of their lives suffered more emotional and behavioral problems than matched controls. Differences and similarities between our findings and observations in patients from Western countries will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 17 publications
2
40
0
5
Order By: Relevance
“…Reviews on QoL and psychological outcomes for adults with DSD cited nine original articles from 1995 to 2004 and fifteen from 2005 to 2014 . In 2015, five novel studies were published . Although these studies address QoL and/or psychological well‐being of individuals with DSD, the results varied greatly.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews on QoL and psychological outcomes for adults with DSD cited nine original articles from 1995 to 2004 and fifteen from 2005 to 2014 . In 2015, five novel studies were published . Although these studies address QoL and/or psychological well‐being of individuals with DSD, the results varied greatly.…”
Section: Introductionmentioning
confidence: 99%
“…In some cultures, fertility is extremely important, as it affects 'marriageability' for women. Egg cell donation may not be allowed and adoption might be uncommon Note that the total number of acknowledgements is greater than the total number of fellows because fellows responded to feedback from two to three experts per question [15][16][17]. A religious official may play a crucial role in management in terms of decision making and with respect to openness on informing family and friends [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Egg cell donation may not be allowed and adoption might be uncommon Note that the total number of acknowledgements is greater than the total number of fellows because fellows responded to feedback from two to three experts per question [15][16][17]. A religious official may play a crucial role in management in terms of decision making and with respect to openness on informing family and friends [16,17]. Options regarding genital surgery involving gonadectomy, hysterectomy or fertility preservation procedures may be subject to religious recommendations [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, two studies have been published from resource-poor countries, where genital surgery for intersex patients is not widely available. A study from Indonesia showed that the intersex patients without medical care did worse than those with medical care (Ediati et al, 2015), but also this article did not disentangle genital surgery per se from other aspects of medical care. A Chinese study of genital surgery in intersex patients reported that''99of133adolescents(74 %)and26of33adults(78 %)thought that it was late to receive surgical intervention'' (Zhang et al, 2013).Thus,inthis study,thedatafromadolescentsseemtoimply a preference for surgery prior to the age of consent.…”
mentioning
confidence: 84%